BIMBINGAN TEKNIS PENGGUNAAN “CONCEPTUAL CHANGE TEXT” PADA PEMBELAJARAN UNTUK MEMINIMALKAN MISKONSEPSI PEMAHAMAN SISWA BAGI GURU DI KELURAHAN BOMBONGAN RT.01 MAKALE - Susanna Vonny Noviana Rante; Marchelina Rante; Asriani Asriani; Josua Laurentius; Pemi Pemi (LPPM Universitas Bina Bangsa, 2023)
This technical guidance partners with teachers who live in Bombongan RT.01 sub-district, Makale District, Tana Toraja Regency, as target partners for teachers who do not know how to use student worksheets that are integrated with the use of Conceptual Change Text . The purpose of implementing this technical guidance is to guide teachers in solving a series of pedagogical and technological problems at target partners related to the use of Conceptual Change Text (CCT). The problems that are the focus of this PKM depart from the findings in a preliminary study conducted in early 2022. The problem in question is that teachers who live in the RT.01 bombongan village do not know how to use conceptual change texts in student worksheets, where the use of CCT properly and correctly can minimize misconceptions experienced by students. The implementation method is by conducting socialization, training and evaluation stages. The results of this community service activity involved 8 teachers including (1) teachers were able to design and use student worksheets that were integrated with CCT properly and correctly, (2) teachers could develop their learning tools to be more creative and innovative